Rancang Bangun Sistem Monitoring Pengukur Dampak Intensitas Cahaya Lampu Buatan terhadap Siklus Sirkadian Manusia pada Ruang Rawat Inap Berbasis Web - Dian Agus Kurniawan (Jurnal Jaringan Telekomunikasi, 2018)
Light is a source of energy that is needed in human life. In hospitals, artificial lighting is very necessary, especially in operating rooms that are impermeable to natural light and must be sterile from room bacteria. Artificial light exposure that does not meet the SNI standard for room lighting causes various problems. Therefore, in this study, a tool to control the intensity of artificial light according to the SNI standard in hospitals was designed. This research uses measurement, calculation and comparison methods. The first measurement is to measure the value of the light intensity of the lamp, then measure the temperature value in the room, the last one is to sterilize the room bacteria. From these measurements, values ??are obtained to be compared in reaching conclusions. From this research, it can be concluded that the monitoring system with the LDR light sensor can read the value of the light intensity properly according to the digital lux meter in the morning at 400 lux, 200 lux in the daytime, and 120 lux at night. Then the DHT-11 sensor can read the temperature value in the room according to the HTC comparison with the morning temperature is 25 degrees, daytime 29 degrees, afternoon 27 days, and night is 24 degrees. To help kill room bacteria, a Utraviolet lamp is used with a light for 2 hours in the morning.